Effects of Common Competing Anions on the Adsorption of As(III) by d-MnO2 and Goethite - Zhu, X.P.; Zhou, H.Q.; Zhou, L.; Bai, D.K. (Asian Journal of Chemistry, 2012)
Batch experiments had been conducted to study the effects of PO43–, HPO42–, H2PO4–, SiO32–, SO42– and Cl– on the adsorption of As(III) by the d-MnO2 and the goethite. Moreover, the influential mechanisms of anions had been discussed. First, when the concentration of As(III) was low (10 mg/L), the effects of PO43– and SiO32– on the adsorption of As(III) by the d-MnO2 were notable and relative small effects of HPO42– and H2PO4– were suggested. PO43–, SiO32– and H2PO4– could affect the adsorption of As(III) by the goethite and the effect of HPO42– could be negligible. Both SO42– and Cl– had negligible competing adsorption to As(III) by the d-MnO2 and the goethite. The effects of anions on the As(III) adsorption by the d-MnO2 were more severe than that by the goethite. Then, when the concentration of As(III) varied from 0-85 mg/L, compared to the blank, all the anions performed their effects to As(III) absorption by the d-MnO2 and the goethite and the effects were more severe in high concentration than that in low concentration. The effects to the goethite were also obvious than that to the d-MnO2 in high concentration. Lastly, for the d-MnO2 and the goethite, SiO32– magnified the effect of PO43–. For the goethite, the combined effect of SiO32– and PO43– was more remarkable. The difference was decided by the structure characteristic of sorbent themselves, the d-MnO2 had more adsorptive capacity while the goethite had strong adsorptive affinity to As(III).